2008
DOI: 10.1021/ja801511n
|View full text |Cite
|
Sign up to set email alerts
|

Facial Symmetry in Protein Self-Assembly

Abstract: Amyloids are self-assembled protein architectures implicated in dozens of misfolding diseases. These assemblies appear to emerge through a "selection" of specific conformational "strains" which nucleate and propagate within cells to cause disease. The short Abeta(16-22) peptide, which includes the central core of the Alzheimer's disease Abeta peptide, generates an amyloid fiber which is morphologically indistinguishable from the full-length peptide fiber, but it can also form other morphologies under distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
472
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(517 citation statements)
references
References 59 publications
37
472
5
3
Order By: Relevance
“…For example, synthetic lipids such as amphiphilic molecules that append sugar, peptide, and nucleic acid moieties as hydrophilic headgroups (24) form hollow cylindrical architectures that can be further used to incorporate metal particles. Also, since the discovery of amyloid-related diseases, scientists have realized that proteins, but also small peptides, have the general property of forming fibers/nanotubes through a self-assembly process (25,26). Therefore, small peptides based on protein sequences have been widely studied for their ability to form well-defined nano-architectures, in particular those forming β-sheet stabilized nanotubes and fibers (27) or fibrous materials from α-helical peptides (28,29).…”
mentioning
confidence: 99%
“…For example, synthetic lipids such as amphiphilic molecules that append sugar, peptide, and nucleic acid moieties as hydrophilic headgroups (24) form hollow cylindrical architectures that can be further used to incorporate metal particles. Also, since the discovery of amyloid-related diseases, scientists have realized that proteins, but also small peptides, have the general property of forming fibers/nanotubes through a self-assembly process (25,26). Therefore, small peptides based on protein sequences have been widely studied for their ability to form well-defined nano-architectures, in particular those forming β-sheet stabilized nanotubes and fibers (27) or fibrous materials from α-helical peptides (28,29).…”
mentioning
confidence: 99%
“…Thus, a higher order geometrical restraint appears to be at play in the DA-(OV)4 structures. This could, for example, arise from a curvature in the "ribbons" such that they form closed nanotubes as has been observed for other amyloids (29)(30)(31). This interpretation would also explain the complete .…”
Section: Resultsmentioning
confidence: 72%
“…The minimum at 214 nm indicates a b-sheet structure. [7] The second minimum at 232 nm results from the stacking of aromatic amino acids and has been reported previously for modified Ab peptide fragments in an aqueous solution. the first minimum at 214 nm is consistent with b-sheet structure [7] and the second minimum at 232 nm is due to the stacking of aromatic amino acids.…”
mentioning
confidence: 55%
“…Studies have shown that early stage aggregates contribute to Ab neurotoxicity and are potentially viable drug targets. [1][2][3] Several fragments of Ab, such as Ab [18][19][20][21][22][23][24][25][26][27][28] , [4] Ab , [5] Ab [16][17][18][19][20][21][22] , [6,7] and Ab 16-20 [8] have been shown to form amyloid fibrils. Recent studies on the hydrophobic core Ab [16][17][18][19][20] suggested that the Lys-Leu-Val-Phe-Phe peptide sequence is critical for fibril formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation